Diversity Of Coleoptera Order Soil Insects In Kerandangan Nature Park Area - Rona Uli Manurung; Mahrus; Tri Ayu Lestari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Diversity Of Coleoptera Order Soil Insects In Kerandangan Nature Park Area TWA Kerandangan is a conservation area located in West Nusa Tenggara Province. There are types of plants and animals in TWA Kerandangan that show acceptable and stable ecosystem conditions based on the role of insects. One type of insect that plays a role in the balance of the ecosystem is soil insects because they are considered good organic matter breakers. The order of soil insects that has a valuable role in the ecosystem is Coleoptera-decomposing wildlife feces. Analysis of their diversity is very important for the sustainability of the ecosystem in Kerandangan TWA. The research method used was pitfall trapping. The diversity level of the Coleoptera diurnal group is included in the low category because it has an average index value of 0.93, and the level of diversity of the Coleoptera nocturnal group is included in the medium category because it has an average index value of 1.34. The dominance index value is < 0.50, which indicates that no species dominates at each station, and the level of evenness is in the low to high category. The most common Coleoptera species found is Onthophagus sp 4, and Onthopagus taurus belongs to the dung beetle group (Scarabaeidae).